PEMBUATAN SISTEM POS BERBASIS IOS UNTUK CAFÉ DIARAKS - Mahotma, I Putu Aldi Satria; Tanamal, Rinabi (JATISI, 2024)
Diaraks is an MSME that engaged in food and beverage sector. To manage their operations, Diaraks café still uses manual record. Transactions that need to be recorded include sales transactions and purchasing transactions. Inside sales transaction, data that recorded by staff includes the number of items bought, price, and grand total of the price. Inside purchasing transaction, recorded data including supplier name, bought goods, and the price. Many times, this manual recording system bringing problems because the recording itself still using paper which in itself can be torn easily or lost and human-error often occurs in the system. Not to mention the inefficient process on stock counting everytime the store closes. From this problem the researcher solution’s is to help Diaraks MSME from design to develop POS application for digitalize Diaraks MSME. The application is iOS Based because Diaraks staffs are using iOS as their main devices. To store the data, cloud database will be used which will later be processed using REST API. The testing conducted using UMUX method. The result of the testing can be concluded that the score obtained is quite good. Implemented feature are good enough to help owner on running their business.